2021
DOI: 10.4314/ahs.v21i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of ear length among normal fetuses of pregnant Igbo women in port Harcourt, Nigeria

Abstract: Background: Fetal ear length measurement has been associated with some clinical values: sonographic marker for chromo- somal aneuploidy and for biometric estimation of fetal gestational age. Objectives: To establish a baseline reference value for fetal ear length and to assess relationship between fetal ear length and gestational age. Methods: Ear length measurements were obtained prospectively from fetuses in 551 normal singleton pregnancies of 15 to 41 weeks gestation. Normal cases were defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…The fetal ear length measured during ultrasound examination has already been the subject of some medical articles which focus on the creation of normal ranges of fetal ear length. When analyzing the normal ranges presented in the literature [6,12,13], it can be shown that the ranges are consistent with the normal ranges of the fetal ear length shown in this paper based on the data from our tertiary center. The available literature focuses mainly on the assessment of the fetal ear in terms of aneuploidy, such as trisomy 13, 18, and 21, and finds quite a statistically significant correlation between aneuploidy and smaller ears in fetuses observed in prenatal life [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The fetal ear length measured during ultrasound examination has already been the subject of some medical articles which focus on the creation of normal ranges of fetal ear length. When analyzing the normal ranges presented in the literature [6,12,13], it can be shown that the ranges are consistent with the normal ranges of the fetal ear length shown in this paper based on the data from our tertiary center. The available literature focuses mainly on the assessment of the fetal ear in terms of aneuploidy, such as trisomy 13, 18, and 21, and finds quite a statistically significant correlation between aneuploidy and smaller ears in fetuses observed in prenatal life [14][15][16][17][18].…”
Section: Discussionsupporting
confidence: 87%
“…Embryogenesis is the stage where the external ear is developed. The ear is visualized most often as a hyperechogenic structure in ultrasound examinations and is most often observed in the longitudinal plane [6]. The structure of the fetal ear which is observed during ultrasound examination is the ear auricle in the longitudinal plane.…”
Section: Discussionmentioning
confidence: 99%